Analisis Daerah Rawan Bencana Kekeringan Berbasis Sistem Informasi Geografis di Kecamatan Selat, Kabupaten Karangasem, Provinsi Bali - Dita Ayu Lorenza; Ni Made Trigunasih; Putu Perdana Kusuma Wiguna (Nandur, 2024)
Selat Subdistrict is one of the areas that experience hydrometeorological disasters, namely drought almost every year, especially during the dry season. The purpose of the study is to classify the level of drought vulnerability and provide directions for mitigating drought disasters that occur in Selat Sub-district. The method used was scoring and weighting, as well as overlaying rainfall, slope, soil type, and land use maps through Geographic Information System (GIS) applications. The results showed that there are five levels of drought vulnerability, namely very low, low, medium, high, and very high. Drought vulnerability in Selat Subdistrict is dominated by moderate drought vulnerability with an area of 2,501.12 ha (34.78%), high drought vulnerability with an area of 2,081.59 ha (28.94%), low drought vulnerability level has an area of 1. 513.64 ha (21.05%), very low drought vulnerability level has an area of 837.16 ha (11.64%), and very high drought vulnerability level has an area of 258.99 ha (3.61%). Mitigation directions for areas with high drought vulnerability can be carried out by constructing dam in Muncan and Peringsari Villages. Mitigation directions for areas with very high drought vulnerability can be done by planting banyan trees and bamboo in the spring area, and harvesting water by collecting rainwater with reservoirs in each residence.